PENERAPAN E-GOVERNMENT MELALUI APLIKASI TANJAK POLRESTA DI KOTA PEKANBARU TAHUN 2021-2022 - Nugroho, Anong Tri Cahyo; ', Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The background to writing this thesis was the limited funds owned by the Pekanbaru City Police, meaning that this application could not be accessed by the entire Smartphone user community. There is a lack of ongoing socialization and education from the Pekanbaru City Police regarding the climbing application to the people of Pekanbaru City and about how to use the application. The purpose of this thesis research is to determine the implementation of E-government through the Tanjak Polresta application in Pekanbaru City in 2021-2022 and the factors inhibiting the implementation of E-government through the Tanjak Polresta application in Pekanbaru City in 2021-2022. The researcher used the research approach used was a descriptive-qualitative research approach. The location of this research was carried out in the Pekanbaru City area. With the types and sources of data in this research, primary data is in the form of interviews and observations conducted by researchers and secondary data is supporting data from the main data, namely the Pekanbaru City Profile, Pekanbaru Police Profile, and Information about the Tanjak Polresta Application. Data collection techniques use interviews and documentation. Meanwhile, data analysis was carried out using qualitative analysis. Based on the results of the research and discussion, it can be concluded that the implementation of e-government through the Tanjak Polresta application in the city of Pekanbaru in 2021-2022 looks quite good as seen from the support, the existence of support from the government such as facilities and infrastructure and competent officers and their support. from society. Capacity: The physical condition of the infrastructure of the Pekanbaru City Police requires maintenance so that existing facilities do not quickly become damaged. Value (Benefits), Implementation of e-government through the Tanjak Polresta application in the city of Pekanbaru in 2021-2022 is that it can make it easier for people to find traffic information. Meanwhile, the inhibiting factors consist of Support (Support) seen in terms of HR or Human Resources, Capacity (Capacity) seen in terms of indications that several facilities and infrastructure are starting to deteriorate and Value (Benefits) seen in terms of lack of socialization and promotion from the Police . Keywords: Implementation, E-Government, and Tanjak Application